Representasi Stereotip Perempuan dalam Musik Dangdut: Hegemoni Kuasa dan Strategi untuk Bertahan - Reni Ferlitasari (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
This research aims to explain the empowerment and capacity of an actor in dangdut music industry. Specifically, it tries to explain the knowledge, involvement, capacity and empowerment of a female singer acting in carrying songs containing what is considered vulgar values or not. Using the social praxeology concept by Bourdieu, this research argues that female singers are dominating actors in terms of dangdut music industry’s growth, though their own positions are not always special, and often enough, at its rock bottom. The stereotype role of a women’s sex and objectification both on the paper or visually can impacts her in social culture system, the self-sexualization of a women actor creates an instruct representation in public. This study uses a qualitative method with data collecting that consists of interviews with 5 female singer actors within dangdut orchestran music industry Alta Musik Pugung